(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Influenza virus is a common human pathogen that has caused serious respiratory illness and death over the past century. In April 2009, a new strain of Influenza virus A H1N1, commonly referred to as “swine flu”, began to spread in several countries around the world, and India confirmed its first case on 16 May 16 2009. Aim: To study the clinical and epidemiological profile of Influenza A H1N1 cases at the Sheth Vadilal Sarabhai General Hospital, Ahmedabad. Materials and Methods: Clinical epidemiological characteristics of Influenza A H1N1 cases from October2018 to February 2019 were retrospectively, descriptively analyzed using data from isolation ward and ICU at the Sheth Vadilal Sarabhai General Hospital, Ahmedabad. Data were Analyzed using MS Excel software. Results: Out of 86 patients studied 36(51.16%) were males and 34(48.83%) were females. Almost half of the patients(47.67%) were in the age group of 12-40 years. 6.9% mortality was found irrespective of age group of the patients. Majority of the patients had bronchopneumonia(39.53%) and bronchovascular prominence(41.86%), and very few of them had lobar consolidation(8.13%). Here we had 63(73.25%) patients in category B and 23(26.74%) patients in category C, all the patients from category C required Ventilatory support either Non invasive or invasive and 16(34.16%) of category B patients also required ventilatory support.98.83% patients had complaint of fever on presentation. 36.04% had breathlessness, 52.32% had coughing, 39.53% had sore throat, 30.23% had generalised weakness, 5.81 % had rhinitis, shock, blood in sputum,1.16% presented with diarrhea. None of them presented with vomiting which is commonly found in other infections of influenza. 15.11% had hypertension, 10.46% had type 2 DM, 9.30% had IHD,10.46% had COPD, 5.81% had hypothyroidism, 4.65% had tuberculosis, 2.32% had CVA. Out of 42 females 4 were pregnant and 1 was post partum. Almost half of the patients(46.51%) required ventilatory support in their course of hospitalization. Conclusion: On the basis of these findings, it can be safely hypothesized that prevalence of Influenza A H1N1 is high in the younger population, and fever, cough and sore throat are the most common symptoms with which the patients usually present. in course of hospitalization half of the patients required ventilatory support which was weaned off later on. Associated comorbid conditions particularly hypertension, diabetes, and COPD were associated with longer duration of hospital stay and complications. Delay in hospital presentation and longer duration of onset symptoms and administration of treatment were linked to poor outcome. Despite of various efforts of government for awareness , patients fails to seek timely medical advise. Over all if presented early after onset of the symptoms can lead to better outcomes.